Supramolecular Presentation of Hyaluronan onto Model Surfaces for Studying the Behavior of Cancer Stem Cells. Issue 10 (21st August 2019) - Pang, Xinqing; O'Malley, Clare; Borges, João; Rahman, Muhammad M.; Collis, Dominic W. P.; Mano, João F.; Mackenzie, Ian C.; S. Azevedo, Helena
Abstract: The supramolecular presentation of extracellular matrix components on surfaces provides a platform for the investigation and control of cell behavior. Hyaluronan (HA) is one of the main components of the extracellular environment and has been shown to play an important role in different cancers and their progression. However, current methods of HA immobilization often require its chemical modification. Herein, a peptide‐based self‐assembled monolayer (SAM) is used as an anchor to immobilize unmodified HA on a bare gold surface, as demonstrated by the quartz crystal microbalance with dissipation monitoring. Peptide‐HA surfaces show increased roughness and greater hydrophobicity when compared to poly‐D‐lysine/HA surfaces, as measured by atomic force microscopy and water contact angle, respectively. Additionally, the peptide SAM can be micro‐contact printed and used to restrict the presentation of HA to specific regions, thereby creating HA patterned surfaces to examine cell behavior. When used for cell culture, these surfaces result in altered adhesion and migration of LUC4 head and neck squamous cell carcinoma cells. These biomimetic surfaces can provide insights into the role of HA in cancer and other diseases and be used as a platform for the development of cell sorting devices. Abstract : The use of peptide‐based self‐assembled monolayers allows the supramolecular presentation of unmodified hyaluronan (HA) for in vitro cell culture . Micro‐contact printing of the peptide permits the formation of patterned HA surfaces for more complex in vitro cell culture studies. The surfaces generated using this platform are used to study the behavior of cancer stem cells on immobilized HA.